Design, synthesis, and evaluation of novel stilbene derivatives that degrade acidic nucleoplasmic DNA-binding protein 1 (And1) and synergize with PARP1 inhibitor in NSCLC cells - Leyuan Chen; Zhonghao Ren; Yunze Zhang; Wenbin Hou; Yiliang Li (Taylor & Francis Group, 2024)
Specifically inducing the degradation of acidic nucleoplasmic DNA-binding protein 1 (And1) is a promising antitumor strategy. Our previous study identified Bazedoxifene (BZA) and CH3 as specific And1 degraders and validated their activity in reversing radiotherapy resistance in vitro and in vivo. However, unelucidated structure-activity relationships and moderate activity have limited their application. In this study, 27 novel CH3 derivatives were designed and synthesised based on the cavity topology of the WD40 domain of And1. Among them, A15 with a "V" conformation significantly induced And1 degradation in NSCLC cells. In addition, this study demonstrated a potential synthetic lethal effect of And1 degraders and PARP1 inhibitors. 1 µM of Olaparib in combination with 5 µM of A15 significantly inhibited the proliferation of A549 and H460 cells. Overall, these compounds are valuable tools for elucidating And1 biology, and their special spatial conformation make them promising candidates for future optimisation studies.